A three-stage algorithm for coordinate controlling of multi-intersection signal. (January 2023) - Zou, Yuanyang; Liu, Renhuai; Li, Ya; Ma, Yingshuang; Wang, Guoxin
Abstract: In the traffic networks, the traffic plans for one intersection are coordinated with those of the adjacent intersections. At the same time, it should be considered that inflow vehicles do not originate at adjacent intersections and that outflow vehicles are the connection links of two adjacent intersections. In this study, first, the inflow vehicles entering the connection link between two adjacent intersections are considered. The outflow vehicles departing the connection links between two adjacent intersections in the traffic network are also considered. Second, a bilevel programming model is introduced. The upper level is designed to optimize the carbon dioxide emissions of the vehicles at intersections and the lower level is designed to match the optimal phases of each inflow lane. To solve the model, a three-stage algorithm, which can obtain the optimization value for the model, is proposed. In the algorithm, the difference between the inflow vehicles and the outflow vehicles estimated by an iter equation. Last, certain methods are employed to compare the proposed model with the algorithm. The results of the numerical experiments indicate that the model and algorithm are effective and that the optimization model and the three-state algorithm could be more reasonable for the plans of multi-intersections than the state-of-the-arts methods. Highlights: The inflow vehicles entering the connection links are considered. The outflow vehicles departing the connection links are considered. A three-stage algorithm is proposed. Lane-changing behavior on a link in the traffic network is considered.